La bibliothèque de ʿAbd al-Ḥayy Kattānī - Ilyass Amharar (Revue des Mondes Musulmans et de la Méditerranée)
‘Abd al-Ḥayy al-Kattānī was born in 1883, into a family of Fassi scholars close to the government. He was the leader of a Brotherhood and also involved in politics; his involvement in the attempted impeachment of Muḥammad V precipitated his exile to Nice, where he passed away in 1962, shortly after having had his possessions confiscated, among which was one of the most prestigious private collections in Morocco, if not in the whole of the Arab world: the Maktaba kattāniyya. Resulting from years of effort and numerous peregrinations of the Moroccan scholar in the Maghreb, the Middle East and Europe, the thousands of rare manuscripts in the library’s catalogue make this one of the richest and most precious collections of the Arab world. After a presentation of ‘Abd al-Ḥayy’s career, this article accurately describes the contents of the library, its influence in the Arab world, its role under the protectorate and its posterity.